Morphology and Electrical Characteristics of Single-Walled Carbon Nanotubes Film Prepared by Air Brush Technique - Hassan, Muhamad Azuddin; Mohamed, Mohd Ambri; Kunaraj, Arulampalam; Yahya, Iskandar (International Journal of Integrated Engineering, 2022)
This study is to investigate the morphology and electrical characteristics of single-wall carbon nanotubes (SWCNTs) thin film deposition using air brush technique. A deposition setup consisting of a conventional artist air brush was developed and used to deposit SWCNT thin films and therefore the resulting film’s characteristics need to be investigated to gauge its suitability in producing uniform monolayer. The SWCNTs used were synthesized via Direct Injection Pyrolytic Synthesis (DIPS) method, with diameters ranging from 0.8 to 3 nm. The substrate was deposited using an airbrush with varying nozzle to study its effect to the resulting SWCNTs thin films’ characteristics. Subsequently, scanning electron microscope (SEM) were used to inspect the morphology and surface topography, and followed by preliminary electrical measurements. The result shows that good dispersion promotes uniform distribution of SWCNTs over large area of glass substrate. Moreover, the electrical measurement revealed that at 1 V, best morphology produced highest current at a nozzle height of 10 mm (15.3 µA) and the lowest current at a nozzle height of 4 mm (3.24 µA). From the results presented, it is demonstrated that conventional artist airbrush setup can be effectively used to deposit monolayer thin film of SWCNT with high degree of uniformity. This research is necessary for the process of depositing-controlled CNT thin film network, which can influence the material characteristics and performance of the variety of CNT-based device applications.